2015
DOI: 10.1186/s40780-015-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the implementation of the computer-assisted HBView system for the prevention of hepatitis B virus reactivation in chemotherapy patients: a retrospective analysis

Abstract: BackgroundScreening for hepatitis B virus (HBV) infection is recommended worldwide for patients receiving systemic chemotherapy in accordance with clinical guidelines, but compliance varies by country and facility. Alert systems may be useful for promoting screening, but it is unclear how effective such systems are. In this study, we investigated HBV screening procedures and their incorporation into treatment regimens following the implementation of an alert system.MethodsAn alert system was introduced at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…positive HBV DNA, which may warrant prompt anti-viral prophylaxis to start with, 16,18,20 as further emphasized by Hwang et al 25 This highlights gaps in HBV screening, suggesting the potential utility of a computer-assisted alert system in aiding to ensure standardized and complete HBV screening prior to rituximab initiation. 26 After rituximab initiation, approximately 40% of patients did not have HBV DNA tests performed during treatment, at initial six month follow-up, and at subsequent follow-ups. As the onset of HBV reactivation is uncertain, current guidelines suggest HBV DNA testing one to three monthly.…”
Section: Discussionmentioning
confidence: 99%
“…positive HBV DNA, which may warrant prompt anti-viral prophylaxis to start with, 16,18,20 as further emphasized by Hwang et al 25 This highlights gaps in HBV screening, suggesting the potential utility of a computer-assisted alert system in aiding to ensure standardized and complete HBV screening prior to rituximab initiation. 26 After rituximab initiation, approximately 40% of patients did not have HBV DNA tests performed during treatment, at initial six month follow-up, and at subsequent follow-ups. As the onset of HBV reactivation is uncertain, current guidelines suggest HBV DNA testing one to three monthly.…”
Section: Discussionmentioning
confidence: 99%
“…Alert systems focusing on HBV have been described previously 7,12 . In the present study, addition of HCV to the test panel in our EAS was also found to be useful for diagnosing new cases of chronic hepatitis C, which led to the start of treatment with direct-acting antiviral agents and sustained virological response.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, testing for viral hepatitis markers before starting these drugs is vital to identify patients at risk of HBV reactivation, who may be candidates for antiviral prophylaxis. In this regard, the use of alert systems has been explored to improve screening rates 7,12 . Sampedro et al reported that use of a computerized physician order entry-based system for patients treated with biologic agents led to a screening rate for HBV markers greater than 85% 7 , a value comparable to the overall percentage of testing in our cohort after the EAS alerts.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Future efforts should focus on the risk of HBV reactivation and optimal strategies for HBV screening and prophylactic antiviral in solid tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alerts in electronic health systems could facilitate HBV screening and early anti-HBV therapy. 16,17 Future efforts should focus on the risk of HBV reactivation and optimal strategies for HBV screening and prophylactic antivirals in patients with solid tumors.…”
mentioning
confidence: 99%